Faktor-faktor yang Mempengaruhi Behavioral Intention Pengguna Mobile Banking BCA: Studi pada Gen Y - Heryanto Heryanto; Miharni Tjokrosaputro (Jurnal Manajemen Bisnis dan Kewirausahaan, 2021)
Recently, the using of mobile banking facilities are increasingly in demand because it considered effective for customers. This research used BCA mobile banking users as respondents. The aim of this research is to determine factors that affects Behavioral Intention of BCA mobile banking users. Sampling from 138 respondents among generation Y by probability sampling method. The researcher collected data by distributing questionnaires to respondents and the data were analyzed by using software SPSS Statistics version 24. The results showed that Effort Expectancy, Performance Expectancy, Social Influence, Facilitating, Security, and Self Efficacy affected positively toward Behavioral Intention for BCA mobile banking users among generation Y. The study could contribute to BCA or other banks to analyze and improve their mobile banking services to increase mobile banking usage among generation Y. Akhir-akhir ini, fasilitas mobile banking semakin diminati karena penggunaannya dianggap efektif bagi pelanggan. Penelitian ini menggunakan nasabah BCA yang pengguna mobile banking sebagai responden. Penelitian ini bertujuan untuk mengetahui berbagai faktor yang berpengaruh pada intensi perilaku pengguna mobile banking BCA. Pengambilan sampel dilakukan pada 138 responden di kalangan generasi Y dengan metode probability sampling. Pengumpulan data melalui penyebaran kuesioner kepada responden dan data dianalisis menggunakan software SPSS Statistics version 24. Hasil penelitian memperlihatkan bahwa Effort Expectancy, Performance Expectancy, Social Influence, Facilitating, Security, dan Self Efficacy berpengaruh positif terhadap intensi perilaku pengguna mobile banking BCA di kalangan Gen Y. Hasil studi ini dapat membantu BCA ataupun industri perbankan untuk menganalisis dan meningkatkan layanan mobile banking untuk meningkatkan penggunaan mobile banking BCA dari generasi Y.